Ergonomic Redesign of Computer Laboratory to Improve Electric Power Performance and Working Efficiency - Wijaya, I Ketut; Adi Putra, I Nyoman; Sutajaya, I Made; Sari Hartati, Rukmi (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 5, No. 1 Januari 2011, 2012)
The current problems in the Computer Laboratory of Udayana UniversityTechnical Engineering Faculty include non-standard room temperature of 28 0 C, nonstandardlight intensity average in the room of 110 lux, seat height of 43 cm and tableheight of 74,50 cm being not adapted to the workers’ anthropometric measurements, anddazzling white-colored curtains. Baseline data on six students after 3-hour workingrevealed the following findings: eye fatigue 81%’ and general fatigue 88%;musculoskeletal complaints 51%; average learning achievement 59.5%, performance16.25%, and efficiency 10.09%. In an effort to improve the working conditions, a totalexperimental ergonomic intervention in the form of redesigning the Computer Laboratorywas introduced.In this study 30 subjects were recruited. The data collected were analyzed by usingdesriptive statistics, normality test, comparability test, and paired-simple t-test with asignificant level of 5%.Total ergonomic intervention has resulted in a decrease of room temperature from280 C to 25.830 C (p<0.05), increase in light intensity from 110 lux to 136.67 lux, decreasein eye fatigue from 81% to 23% (p<0.05), decrease in general fatique 88% to 41%,decrease in musculoskeletal complaints from 51% to 11% (p<0.05), increase in learningachievement score from 59.5% to 89.5% (p<0.05), increase in performance from 16.25%to 41.25%, and increase in efficiency from 10.09% to 75.09% (p<.05).The results of this study revealed that appropriate total ergonomic intervention in acomputer laboratory had succeeded in improving the quality of working and performanceof the workers.
Keywords: Ergonomic redesign, efficiency in electric power performance and use, learning and working efficiency